Effects of metal ion-doping on the characteristics and photocatalytic activities of TiO₂ nanotubes - Shaona Wang; Rongfang Yuan; Beihai Zhou; Huanhuan Guan (Functional Materials, 2018)
Ion-doped TiO₂ nanotubes were synthesized via a hydrothermal method and characterized by transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy and specific surface areas. The binding energies of Cu²⁺, V²⁺, and Zn²⁺ indicated that the doping ions existed as Cu²⁺, V⁵⁺, and Zn²⁺, respectively. With the increase of the calcination temperature, the intensity of the anatase phase decreased and the BET surface area decreased. The extent of anatase phase increased with the increasing the calcination temperature, and then decreased. The highest catalytic activity for the un-doped TiO₂ nanotubes was observed at a calcination temperature of 500 °C, with a Rhodamine B (RB) removal efficiency of 98.1%. The removal efficiency of RB was 98.2% when Cu2²⁺-doped catalyst calcined at 450 °C was added, 0.1% higher than the un-doped TiO₂ nanotubes. The highest photocatalytic activity was obtained in the presence of Zn2+-doped catalyst calcined at 550 °C, where 98.7% of RB was removed.